MENGUKUR PERILAKU KONSUMTIF MILENIAL DALAM MENGGUNAKAN PAYLATER - Permana, Gusi Putu Lestara (Jurnal Riset Akuntansi Politala, 2025)
Consumptive behavior related to using Pay later services or paying later is a fairly common problem and carries certain risks. Several issues related to consumer behavior in using Paylater. Increased debt. Using Paylater can encourage someone to continue buying goods or services without considering how large the debt is being built up. This research uses quantitative research methodology. Data was collected using a questionnaire technique (questionnaire) with a Likert scale. The results of this research suggest that this construct is only able to partially explain millennial consumer behavior in using pay later because the three primary constructs are the perception of ease of use of income, perception of benefits of income, intensity of use of the wasteful lifestyle and are rejected based on test results which indicate that the construct This is not able to measure millennial consumer behavior in using pay later. However, the perception of ease of use towards the intensity of use and income towards consumptive lifestyle from these two constructs were accepted based on test results, which indicated that this construct could measure millennial consumptive behavior in using pay later.